A contemporary approach to sedation during regional anaesthesia in gynaecology (Pain medicine, 2020)
Safe and adequate sedation during regional anesthesia is one of the issues at the current time. According to the basic principles of modern anesthesiology, safe and effective sedation should protect the patient’s psycho-emotional sphere, provide absence of awareness, pain and fear during surgery as well as nausea and vomiting in the postoperative period. At the same time, it should neither cause respiratory depression and haemodynamics changes, nor be accompanied by a slow recovery of psychomotor function.After studying modern literature and analyzing our own observations, we reached the point that sedation with dexmedetomidine rather than propofol is more preferred during regional anaesthesia. Sedation with dexmedetomidine decreases frequency of cognitive impairment in the early postoperative period, intensity of the pain syndrome, and has beneficial effect on recovery and activation after surgery. Additionally, it is associated with lower risk of hypoxemia and arterial hypotension during surgery.
Keywords: sedation; regional anesthesia; dexmedetomidine